Oh, what a lovely sequence of numbers you have there! To find the pattern and the nth term, we can see that each number is increasing by adding consecutive even numbers (2, 4, 6, ...). So, the nth term can be found using the formula n^2 + 9. Keep exploring and creating, my friend!
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the pattern is that each term is obtained by adding consecutive even numbers starting from 2. The nth term can be calculated using the formula nth term = 2 + n(n-1), where n represents the position of the term in the sequence. So, for the given sequence, the nth term would be 2 + n(n-1).
f(n) = 14 - 6n -6n+20
[ 6n + 8 ] is.
The nth term is: 3n+2 and so the next number will be 20
t(n) = 10 - 6n where n = 1, 2, 3, ...
20 - (3 * (n - 1))
f(n) = 14 - 6n -6n+20
They are: nth term = 6n-4 and the 14th term is 80
560
[ 6n + 8 ] is.
It is: 26-6n
The nth term is: 3n+2 and so the next number will be 20
t(n) = 10 - 6n where n = 1, 2, 3, ...
20 - (3 * (n - 1))
a (sub n) = 11 + (n - 1) x d
The nth term is: 5n
The nth term of the sequence is expressed by the formula 8n - 4.
8 + (74 x 6) = 75th term. nth term = 8 + 6(n-1)